The Influence of Motivation, Stress and Finance on Employee Job Satisfaction at PT Kriya Lab Indonesia - Christy, Gita; Christie, Gracia Paskalis (Yayasan Az Zukhruf Cendikia, 2025)
Purpose - The research aims to test, analyze and determine the influence of motivation, stress, and finances on employee job satisfacion at PT Kriya Lab Indonesia. Design/mothodology/approach - This research uses primary data. The data collected who work at PT Kriya Lab Indonesia. This data analysis was carried put using Partial Least Square (PLS) software with moderated regression analysis. The design of this research is non probability sampling. Findings - From this research, it can be seen that motivation has a positive effect on job satisfaction, and stress has a negative effect on job satisfaction, then finances has a positive effect on job satisfaction. Research limitations/implications - This research is very relevant to the world of work today, where the motivation, stress levels, and financial conditions are key factors that influence employee job satisfaction. This allows the research results to provide practical guidance for organizations to increase employee productivity and well being. This research has the potential to add scientific insight in the field of management. This study has several limitations that should be consired when interpreting the results. First, all research variables, namely motivations, stress, finances as independent variables, job satisfaction as the dependent variable are measured using sample, so data is difficult to obtain. Another obstacle is when all research variables are measured using questionnaire, so the data obtained is only the respondent’s opinion. Respondents were obtained through a questionnaire tha had been distributed via the google form link so that the questionnaire obtained was not guided in detail in filling it out.